2016
DOI: 10.1016/j.neuroimage.2016.03.074
|View full text |Cite
|
Sign up to set email alerts
|

Alpha power indexes task-related networks on large and small scales: A multimodal ECoG study in humans and a non-human primate

Abstract: Performing different tasks, such as generating motor movements or processing sensory input, requires the recruitment of specific networks of neuronal populations. Previous studies suggested that power variations in the alpha band (8–12 Hz) may implement such recruitment of task-specific populations by increasing cortical excitability in task-related areas while inhibiting population-level cortical activity in task-unrelated areas (Klimesch et al., 2007; Jensen and Mazaheri, 2010). However, the precise temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 76 publications
7
58
2
2
Order By: Relevance
“…This interpretation is in line with the inhibitory role of alpha oscillations (De Pesters et al, 2016, Klimesch et al, 2007, Pfurtscheller and Da Silva, 1999). …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This interpretation is in line with the inhibitory role of alpha oscillations (De Pesters et al, 2016, Klimesch et al, 2007, Pfurtscheller and Da Silva, 1999). …”
Section: Discussionsupporting
confidence: 83%
“…This property can be expressed, for instance, in the form of an inhibition of distant task-irrelevant regions by means of an increase of alpha activity (De Pesters et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…This is in line with recent findings from human and animal intracranial recordings demonstrating the spatial specificity of alpha activity in the auditory domain. Task‐relevant alpha power is differentially modulated within the auditory system in accordance with differential sound input and relates to population‐level activity (de Pesters et al, ). Thus, the spatial tuning reported here potentially reflects the allocation of spatial attention by setting the gain in a regionally specific sense such that processing of upcoming targets are facilitated while distractors are inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that the power or phase of oscillatory activity modulates the level of cortical activity or behavioral performance [6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32] and hence plays a central role in the dynamic modulation of cortical function in response to varying task demands [33, 34, 35]. Specifically, these and other studies have consistently reported that during times when oscillatory power is low or during times of an oscillatory trough, the probability of action potential firing rate, broadband gamma augmentation, or higher behavioral performance is increased 2 .…”
Section: Introductionmentioning
confidence: 99%